The role of dunes in flow resistance in a large and a small river. The case of the Paraná and Tercero rivers, Argentina. Issue 3 (4th May 2022) - Latosinski, Francisco G.; Amsler, Mario L.; Vionnet, Carlos A.; Heredia Ligorria, Ana I.; Szupiany, Ricardo N.; Diaz Lozada, José M.; García, Carlos M.; García, Marcelo H.
Abstract : The dynamics of sandy rivers is a complex phenomenon linking the interactions between dunes, flow and sediment transport. Despite an existing large amount of research, few comparative studies exist for rivers with major hydro-sedimentological differences. This work uses detailed dune measurements from the Paraná and Tercero rivers, Argentina. Significant differences were found in the representative roughness height scale, dune steepness, lee angles, velocity profiles and flow recirculation. It is found that whereas the hydraulic resistance for the Tercero River scales with the size of large dunes, the Paraná River needs to develop an intermediate roughness scale (the small superimposed dunes) to accommodate the required balance between gravity and friction. Suspended bed sediment increase is inversely related to the dune steepness and lee side angles as advanced by previous findings. The suspension number seems to be a paramount metric that helps explain differences regarding dune geometry within a wide range of flow conditions.